Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Evaluate [tex]\( ab - 0.5b \)[/tex] when [tex]\( a = 1 \)[/tex] and [tex]\( b = 5 \)[/tex].

Sagot :

Sure! Let's evaluate the expression [tex]\( ab - 0.5b \)[/tex] step by step, given that [tex]\( a = 1 \)[/tex] and [tex]\( b = 5 \)[/tex].

1. Start by substituting the values of [tex]\( a \)[/tex] and [tex]\( b \)[/tex] into the expression:
[tex]\[ ab - 0.5b = 1 \cdot 5 - 0.5 \cdot 5 \][/tex]

2. First, multiply [tex]\( a \)[/tex] and [tex]\( b \)[/tex]:
[tex]\[ 1 \cdot 5 = 5 \][/tex]

3. Next, multiply 0.5 and [tex]\( b \)[/tex]:
[tex]\[ 0.5 \cdot 5 = 2.5 \][/tex]

4. Then, subtract the result of [tex]\( 0.5b \)[/tex] from the result of [tex]\( ab \)[/tex]:
[tex]\[ 5 - 2.5 = 2.5 \][/tex]

So, the evaluated result of the expression [tex]\( ab - 0.5b \)[/tex] when [tex]\( a = 1 \)[/tex] and [tex]\( b = 5 \)[/tex] is:
[tex]\[ \boxed{2.5} \][/tex]